2008
DOI: 10.1590/s1806-37132008001100002
|View full text |Cite
|
Sign up to set email alerts
|

Influência do biofármaco DNA-hsp65 na lesão pulmonar induzida por bleomicina

Abstract: Objective: To evaluate the effects of immunization with a DNA-hsp65 vaccine in an experimental model of pulmonary fibrosis. Methods: A total of 120 male C57BL/6 mice were distributed into four groups: SS, injected with saline (placebo) and then receiving intratracheal (IT) instillation of saline; SB, injected with saline (placebo) and then receiving IT instillation of bleomycin; PB, treated with plasmid only, without bacterial genome, and then receiving IT instillation of bleomycin; and BB, treated with the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…The results of immunogenicity and therapeutic efficacy in experimental models of TB in cell culture and in animals showed that the preventive and therapeutic activities of DNAhsp65 are associated with a series of factors related to the activation of the innate and adaptive immune systems. The results of immunogenicity and efficacy tests demonstrated that the vaccine activates DCs, macrophages, and B lymphocytes; activates CD4, CD8, and γδT cells; controls the activation of lymphocytes of the Th1, Th17, and Treg patterns; guides a Th1 immune response profile, with high IFN-γ signaling; produces cytokines and activation molecules needed to control the growth of bacilli; and activates fibrosis control and resolution of the granulomatous process (20,85). Due to the great immunotherapeutic potential of DNAhsp65 for TB, we are starting a clinical study to test the safety, maximum tolerated dose, immunogenicity, and preliminary efficacy of this product as a therapeutic adjunct for the treatment of patients with MDR-TB (DNAhsp65 + drugs).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of immunogenicity and therapeutic efficacy in experimental models of TB in cell culture and in animals showed that the preventive and therapeutic activities of DNAhsp65 are associated with a series of factors related to the activation of the innate and adaptive immune systems. The results of immunogenicity and efficacy tests demonstrated that the vaccine activates DCs, macrophages, and B lymphocytes; activates CD4, CD8, and γδT cells; controls the activation of lymphocytes of the Th1, Th17, and Treg patterns; guides a Th1 immune response profile, with high IFN-γ signaling; produces cytokines and activation molecules needed to control the growth of bacilli; and activates fibrosis control and resolution of the granulomatous process (20,85). Due to the great immunotherapeutic potential of DNAhsp65 for TB, we are starting a clinical study to test the safety, maximum tolerated dose, immunogenicity, and preliminary efficacy of this product as a therapeutic adjunct for the treatment of patients with MDR-TB (DNAhsp65 + drugs).…”
Section: Discussionmentioning
confidence: 99%
“…Some monoclonal antibody treatments are currently available that target profibrotic cytokines or activate Th1 cells as a novel immunopharmacological intervention (84). In this context, treatment with DNAhsp65 in an experimental model of pulmonary fibrosis reduced the deposition of noncollagenous matrix (85), and when associated with anti-TB drugs, it was more efficient in reducing tissue damage, resulting in reduced fibrosis during synergistic immunochemotherapy in experimental TB (20). Taken together, these data indicate that treatment with DNAhsp65 was effective in reducing tissue damage caused by excessive ECM deposition.…”
Section: The Fibrotic Processmentioning
confidence: 99%
“…Specimens were processed, embedded in paraffin and cut into for to six lm sections and stained with haematoxylin and eosin (H&E). For evaluation of collagen fibres in the pulmonary parenchyma, the slides were stained with Picro Sirius [41]. The surface density of collagen fibres in the lung was determined by optical density by image analysis.…”
Section: Methodsmentioning
confidence: 99%